Psychometric evaluation of modified spinal muscular atrophy functional rating scale (SMAFRS) in adult patients using Rasch analysis. Issue 3 (15th January 2023) - Sadjadi, Reza; Kelly, Kristina; Glanzman, Allan M.; Montes, Jacqueline; Linsenmayer, Matthew; Tellez, Marco; Bartlett, Amy; Heintzman, Sarah; Kolb, Stephen J.; Arnold, W. David; El‐Sheikh, Bakri
Abstract: Introduction/Aims: The Spinal Muscular Atrophy Functional Rating Scale (SMAFRS) was first developed as a secondary functional outcome measure to detect changes over time in patients with spinal muscular atrophy (SMA) in clinical trials. Its modified version evaluates 10 activities of daily living. The aim of the study was to analyze modified SMAFRS data using item response theory psychometric models. Methods: A total of 253 responses from 41 adult patients with ambulatory and non‐ambulatory SMA types 2, 3, and 4 were analyzed. Rasch analysis was used to explore item‐person targeting, fit statistics, category response functioning, dimensionality, and differential item functioning. Results: Most items had good fitting with the exception of "toileting" and "respiratory." There were no major floor or ceiling effects, and most items covered a good range of disability with only a negligible breech of uni‐dimensionality from eating, dressing, and respiratory items. Differential item function highlighted differences in toileting, turning, transferring, walking, and respiratory items between ambulatory and non‐ambulatory populations. Discussion: Despite subtle misfitting of certain items, mainly related to respiratory and bulbar function, overall modified SMAFRS remained a psychometrically stable and unidimensional outcome measure. There were some differences in measuring properties of certain functional items between ambulatory and non‐ambulatory items that need to be taken into consideration in clinical trial design. Overall, the modified SMAFRS is a psychometrically reliable tool in assessment of adult patients with SMA.